Antibiotic use during the first 6 months of COVID‐19 pandemic in Iran: A large‐scale multi‐centre study. (21st August 2022) - Salehi, Mohammadreza; Khalili, Hossein; Seifi, Arash; Davoudi, Hamidreza; Darazam, Ilad Alavi; Jahangard‐Rafsanjani, Zahra; Mohammadnejad, Esmaeil; Heydari, Behrooz; Siahkaly, SaeedReza Jamali Moghadam; Tabarsi, Payam; Kalantari, Saeed; Menshadi, Seyed Ali Dehghan; et al.
Abstract: What is known and objective: Although antibiotics are ineffective against viral infections, epidemiological studies have revealed that the COVID‐19 pandemic resulted in the overuse of antibiotics and disruption of antimicrobial stewardship programmes. We investigated the pattern of antibiotic use during the first 6 months of the COVID‐19 pandemic in Iran. Methods: A multi‐centre retrospective study was designed to investigate the use of 16 broad‐spectrum antibiotics in 12 medical centres. The rate of antibiotic use was calculated and reported based on the Defined Daily Dose (DDD) per 100 hospital bed‐days. The bacterial co‐infection rate was also reported. Results and discussion: Totally, 43, 791 hospitalized COVID‐19 patients were recruited in this study. It was found that 121.6 DDD of antibiotics were used per 100 hospital bed‐days, which estimated that each patient received approximately 1.21 DDDs of antibiotics every day. However, the bacterial co‐infections were detected only in 14.4% of the cases. A direct correlation was observed between the rate of antibiotic use and mortality ( r [142] = 0.237, p  = 0.004). The rate of antibiotic consumption was not significantly different between the ICU and non‐ICU settings ( p  = 0.15). What is new and conclusion: In this study, widespread antibiotic use was detected in the absence of the confirmed bacterial coinfection in COVID‐19 patients. This over‐consumption of broad‐spectrum antibiotics may be associated with increased mortality in hospitalized COVID‐19 patients, which can be an alarming finding. Abstract : Detailed consumption rate (ACI) of each antibiotic in 12 included MCs during the first 6 months of COVID‐19 pandemic in Iran. ACI, antibiotic consumption index; DDD per 100 bed‐days.